CoO (at) Ag nano-enzyme as well as preparation method and application thereof
By preparing CoO@Ag nanoenzyme and electrospinning technology, CoO@Ag-PAN (CAP) fiber membrane was developed, which solved the problem of the inability to reuse and lack of self-cleaning performance of existing masks, and achieved efficient antibacterial and real-time protection. It was suitable for protective equipment to improve personal and public health.
Patent Information
- Application Number
- CN202510258160.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-06
AI Technical Summary
Existing masks cannot be reused after use, and commercial masks lack self-cleaning properties, resulting in the accumulation of bacteria and microorganisms on the surface of the mask, affecting personal health and public safety.
By preparing CoO@Ag nanoenzyme and combining electrospinning technology, CoO@Ag-PAN (CAP) fiber membrane with excellent intrinsic antibacterial ability was prepared, and applied to masks to achieve efficient antibacterial and real-time protection.
The mask can quickly kill bacteria under both light and light conditions, achieving real-time protection, maintaining high filtration efficiency and recyclability, and avoiding microplastic pollution.
Smart Images

Figure CN119750660A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional material preparation, and specifically relates to a CoO@Ag nanozyme and a preparation method thereof, as well as application of the CoO@Ag nanozyme in the preparation of masks with high-efficiency antibacterial, real-time protection and reusable functions. Background Art
[0002] Air pollution caused by particulate matter and pathogenic bacteria seriously endangers the ecological environment and human health. As one of the non-drug intervention measures for respiratory infections, the use of masks is an important way to prevent infection and transmission. However, masks cannot be reused or recycled after use, which exacerbates the problem of microplastics. In addition, commercial masks are usually composed of polypropylene (PP) meltblown non-woven fabric cores, which lack self-cleaning properties. Long-term use of masks can lead to the accumulation and reproduction of bacteria and other microorganisms on their surfaces, which may harm personal health and cause secondary transmission. Nanomaterials with antimicrobial properties (such as metal materials, carbon materials, and polymers) have been used in textiles to develop personal protective equipment that can effectively fight pathogens. However, the preparation of some bactericides is complicated and consumable. Moreover, the traditional method of impregnating nanomaterials into fabrics has great limitations, which easily leads to the separation of nanomaterials and insufficient surface functionalization. In contrast, the preparation of fiber membranes loaded with nanomaterials by electrospinning has stronger dispersibility, stability, and load controllability, providing great potential for the development of antimicrobial protection devices. Therefore, there is an urgent need to design and prepare simple, low-cost nanomaterials with excellent inherent antibacterial properties, and to develop highly effective antibacterial, real-time protective, and reusable masks using spinning methods, which is crucial to improving personal and public health. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a CoO@Ag nanozyme and a preparation method and application thereof. The present invention prepares CoO@Ag nanozyme with excellent antibacterial performance through a simple process, and applies the CoO@Ag nanozyme to the preparation of masks. The prepared masks have excellent inherent antibacterial ability and achieve high performance and real-time protection effects.
[0004] To achieve the above object, the technical solution adopted by the present invention is: The first aspect of the present invention is to provide a method for preparing CoO@Ag nanozyme, comprising the following steps: The cobalt salt and the stabilizer are dissolved in water to obtain a cobalt salt solution. A reducing agent is added to the cobalt salt solution and stirred for reaction. Then, a silver nitrate solution is added and stirred continuously. Finally, a quencher is added to quench the reaction. The obtained product is washed three times with anhydrous ethanol and deionized water respectively, collected by centrifugation and dried, and recorded as CoO@Ag nanozyme.
[0005] In a further embodiment, the cobalt salt is a water-soluble salt such as cobalt nitrate, cobalt sulfate or cobalt chloride; the stabilizer is trisodium citrate; the reducing agent is sodium borohydride, which is pre-cooled before use; and the quenching agent is anhydrous ethanol.
[0006] In a further embodiment, the molar ratio of the cobalt salt to silver nitrate is (1-10):1, and more preferably 8:1.
[0007] The reaction process involved in the preparation of CoO@Ag nanozyme in the present invention is described by the following reaction formulas (1) and (2): Co 2+ + 2BH4 - = Co + H2 + 2BH3(1) 2Co + 4Ag + + O2 = 4Ag + 2CoO(2) First, NaBH4 solution is used as a reducing agent to reduce Co in the cobalt salt solution. 2+ Reduced to Co nanoparticles. + The standard redox potential of Ag (0.799 V vs. standard hydrogen electrode (SHE)) is much higher than that of Co 2+ / Co redox couple (-0.277 Vvs. SHE), so, when silver nitrate was subsequently added to the reaction solution, the Co nanoparticles were immediately oxidized to Co 2+ , forming CoO. At the same time, Ag + It is reduced to Ag and binds to the surface of CoO nanozyme through electrostatic interaction. During the reaction, sodium citrate acts as a stabilizer and dispersant.
[0008] The second aspect of the present invention is to prepare CoO@Ag-PAN (CAP) fiber membrane, and the CoO@Ag nanozyme prepared in the first aspect is used to prepare the CAP fiber membrane, comprising the following steps: Polyacrylonitrile powder and CoO@Ag nanozyme were dispersed in a solvent to obtain a mixed solution. After removing the bubbles in the mixed solution, a functional fiber membrane was prepared by electrospinning technology, named CAP film. The conditions for electrospinning were: voltage of 12 kV, constant feed rate of 0.15 mm / min, roller receiver speed of 140 rpm, and the distance between the roller and the needle tip of 15 cm.
[0009] The third aspect of the present invention is to use the CAP fiber membrane prepared in the second aspect as a sterilization and filtration intermediate layer in a mask, comprising the following steps: the prepared CAP fiber membrane is pressed into shape by mechanical external force and used as a sterilization and filtration layer to replace the intermediate layer of an ordinary commercial mask.
[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The CoO@Ag nanozyme provided by the present invention is prepared by a room temperature reduction method. The required reaction equipment is simple and the reaction conditions are mild. The prepared CoO@Ag nanozyme has excellent antibacterial properties and is suitable for large-scale application and production.
[0011] (2) The present invention combines electrospinning technology to apply CoO@Ag nanozyme to CAP fiber membrane, and successfully prepares fiber membrane with excellent inherent antibacterial ability. Its preparation is simple, the raw materials are easily available, it can be prepared in general chemical laboratories, and it is easy to promote.
[0012] (3) The CAP fiber membrane prepared by the present invention can show excellent real-time antibacterial performance without any auxiliary materials, and can instantly generate a large amount of surface-bound singlet oxygen ( ) and hydroxyl radicals ( ), which quickly inactivates bacteria. CAP masks also have strong inherent antibacterial properties and can almost kill bacteria within 20 minutes. Under simulated sunlight, it only takes 90 seconds to completely kill bacteria, greatly shortening the sterilization time and achieving the real-time protection effect of the mask indoors and outdoors (with or without light sources). At the same time, CAP masks maintain a high filtration efficiency and excellent recyclability. It is worth noting that the CAP mask does not heat up significantly even when exposed to sunlight for 3 hours in winter, indicating that it does not cause thermal damage to the human body during normal outdoor use. This study is conducive to promoting the daily application scenarios of multi-functional masks. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 TEM image and EDS image of CoO@Ag nanozyme prepared in Example; Figure 2 The singlet oxygen ( 1 O2) and hydroxyl radicals ( )’s yield test results; Figure 3 This is a test diagram of the antibacterial performance of the CoO@Ag nanozyme prepared in Example; Figure 4 This is a biocompatibility test diagram of the CoO@Ag nanozyme prepared in the example; Figure 5 SEM images, FT-IR images, stress-strain curves, XRD images, and TGA analysis images of PAN and CoO@Ag-PAN (CAP) fiber membranes prepared in the application examples; Figure 6 The antibacterial performance test diagram of PAN and CAP3 membranes prepared in the application example; Figure 7 This is a performance test comparison chart of the CAP3 membrane mask made in the application example and the ordinary commercial mask; Figure 8 The infrared images of the photothermal heating of the PAN and CAP3 films prepared in the application example under natural light; Fig. 9 This is a test chart of the antibacterial cycle performance of the CAP3 membrane prepared in the application example. DETAILED DESCRIPTION
[0014] In conjunction with the accompanying drawings in the embodiments of the present invention, the technical scheme in the embodiments of the present invention is further described in detail. The specific embodiments described below are only used to explain the present invention and are not intended to limit the present invention. The reagents and raw materials used in the following examples are all commercially available products and are commercially available.
[0015] Example 1 The preparation of CoO@Ag nanozymes with high intrinsic antibacterial ability includes the following steps: Dissolve 0.46 mmol of cobalt nitrate hexahydrate in 40 mL of aqueous solution, then add 10 mL of 2 mM trisodium citrate solution, stir magnetically for 30 minutes, quickly add 10 mL of 8 mM sodium borohydride solution precooled from a 4 °C refrigerator, and continue stirring for 5 minutes. Inject 5 mL of 2 mg / mL silver nitrate solution, continue to react for 10 minutes, and then quench the reaction with anhydrous ethanol. The obtained product was washed three times with anhydrous ethanol and deionized water, collected by centrifugation, and finally dried in a vacuum oven at 60 °C, recorded as CoO@Ag nanozyme.
[0016] Other embodiments In Example 1, the molar ratio of cobalt nitrate hexahydrate to silver nitrate is about 8:1. In other examples, the amounts of cobalt nitrate hexahydrate and silver nitrate are adjusted so that the molar ratios of cobalt nitrate hexahydrate and silver nitrate are 1:1, 4:1, 6:1, and 10:1, respectively. The other processes are the same as in Example 1. Under different amounts of reactants, the corresponding CoO@Ag nanozymes are prepared respectively.
[0017] Product structure characterization and performance testing Figure 1 The TEM and EDS images of the CoO@Ag nanozyme prepared in Example 1 are shown in Figure A. Figure A is the TEM image of the CoO@Ag nanozyme, Figure B is the EDS image of Co in the CoO@Ag nanozyme, Figure C is the EDS image of Ag in the CoO@Ag nanozyme, and Figure D is the EDS image of O in the CoO@Ag nanozyme. Figure 1 It can be seen that Ag is mainly distributed on the CoO surface, and Co, Ag, and O coexist.
[0018] Figure 2 The CoO@Ag nanozymes prepared by using cobalt nitrate hexahydrate and silver nitrate in different dosage ratios under the conditions of no light and 1 Singlet oxygen under solar simulator irradiation ( ) and hydroxyl radicals ( )'s yield test results, Figure 2 Figure A in the middle is The yield test results are shown in Figure B. Yield test results. Figure 2 It can be seen that with the increase of cobalt content, the ability to generate ROS gradually increases. When the molar ratio of cobalt nitrate hexahydrate to silver nitrate in the reactant reaches 8:1, the yield of ROS reaches the best, and even without light, 44.20% can be generated within 2 minutes. and 16.91% , while in 1 The yield under the irradiation of the solar simulator increased to 60.35% and 18.69% accordingly. After that, although the amount of cobalt nitrate hexahydrate added continued to increase, the ability to generate ROS decreased. This phenomenon may be attributed to the formation of a more stable CoO and Ag composite structure state at the optimal molar ratio, resulting in the best catalytic performance. Therefore, the subsequent performance tests and CAP fiber membrane preparation were carried out at this ratio.
[0019] Figure 3 This is a test diagram of the antibacterial performance of the CoO@Ag nanozyme prepared in Example 1. Escherichia coli and Staphylococcus aureus were selected as the test objects, where Figure A is a digital image of CoO@Ag co-cultured with Staphylococcus aureus and Escherichia coli under light-free conditions, Figure B is a digital image of the antibacterial efficiency of CoO@Ag co-cultured with Staphylococcus aureus and Escherichia coli under light-free conditions, and Figure C is a digital image of the antibacterial efficiency of CoO@Ag co-cultured with Staphylococcus aureus and Escherichia coli under light-free conditions. 2 Digital images of CoO@Ag co-cultured with Staphylococcus aureus and Escherichia coli under simulated sunlight. D is at 1 W / cm 2 Antibacterial efficiency of CoO@Ag co-cultured with Staphylococcus aureus and Escherichia coli under simulated sunlight. Figure 3 As can be seen from Figures A and B, without external light source stimulation, CoO@Ag nanozyme can achieve 100% antibacterial efficiency within 11 minutes, indicating that it has excellent autonomous antibacterial properties. Figure 3 It can be seen from Figures C and D that at 1 W / cm 2 Under simulated sunlight, there were almost no surviving colonies in 5 minutes.
[0020] Figure 4This is a biocompatibility test graph of the CoO@Ag nanozyme prepared in the embodiment. A549 cells and Hela cells were selected as test objects, wherein Figure A is a staining graph of the co-culture of CoO@Ag and A549 cells, Figure B is a survival rate graph of the co-culture of CoO@Ag and A549 cells, Figure C is a staining graph of the co-culture of CoO@Ag and Hela cells, and Figure D is a survival rate graph of the co-culture of CoO@Ag and Hela cells. Biocompatibility is a key issue in practical applications. Tests show that CoO@Ag nanozyme has low cytotoxicity, indicating that it has good biocompatibility.
[0021] Application Examples The preparation of the functionalized fiber membrane CoO@Ag-PAN (CAP) includes the following steps: 1.2 g of polyacrylonitrile powder and 0.4 mg, 0.8 mg, and 1.6 mg of CoO@Ag nanozymes were dispersed in 10 mL of N,N-dimethylformamide solution, respectively, and stirred evenly until the bubbles in the solution disappeared completely. Then the solution was injected into a 10 mL syringe, and a 20# stainless steel needle was connected to the needle end of the syringe for electrospinning. The spinning conditions were as follows: voltage of 12 kV, constant feed rate of 0.15 mm / min, roller receiver speed of 140 rpm, and the distance between the roller and the needle tip was 15 cm. The obtained functionalized nanofiber film was named CAP film. The CoO@Ag nanozyme content in the CAP film was named CAP1, CAP2, and CAP3 fiber membranes from low to high. For comparison, pure PAN fiber membranes were also prepared by the same electrospinning process.
[0022] The prepared fiber membrane is pressed into shape by mechanical external force, and a functional mask can be obtained by using it as a sterilization filtration layer to replace the middle layer of an ordinary commercial mask.
[0023] Figure 5The SEM images, FT-IR images, stress-strain curves, XRD images, and TGA analysis images of the prepared PAN and CAP fiber membranes are shown in Figure A, Figure B, Figure C, Figure D, Figure E, and Figure E. It can be seen that the CoO@Ag-PAN (CAP) fiber membrane loaded with CoO@Ag nanozyme was prepared by electrospinning. Compared with pure PAN fibers, the diameters of CAP1, CAP2, and CAP3 fibers loaded with CoO@Ag increased and the surface became rougher, indicating that CoO@Ag was successfully loaded on the surface of PAN fibers. The stress-strain curves show that CAP1, CAP2, and CAP3 fiber membranes all exhibit better mechanical properties, and the tensile strength of CAP3 membrane is stronger. Thermogravimetric analysis also shows that CAP3 membrane has better thermal stability. All subsequent tests of antibacterial properties used CAP3 membranes with a CoO@Ag content of 1.6 mg, and the CAP3 membranes were subsequently used as mask model applications.
[0024] Figure 6 Figure 1 shows the antibacterial performance test of PAN and CAP3 membranes prepared in the application example. Staphylococcus aureus and Escherichia coli were selected as the test objects. Figure A is a digital image of Staphylococcus aureus cultured under lightless conditions, Figure B is a survival rate graph of Staphylococcus aureus cultured under lightless conditions, and Figure C is a digital image of Staphylococcus aureus cultured under 1 W / cm 2 Digital images of Staphylococcus aureus cultured under simulated sunlight. D is at 1 W / cm 2 Figure 1 shows the survival rate of Staphylococcus aureus cultured under simulated sunlight. Figure E shows the digital image of Escherichia coli cultured under lightless conditions. Figure F shows the survival rate of Escherichia coli cultured under lightless conditions. Figure G shows the survival rate of Escherichia coli cultured under 1 W / cm 2 Digital image of Escherichia coli cultured under simulated sunlight. H image shows the temperature at 1 W / cm 2 The survival rate of Escherichia coli cultured under simulated sunlight. After the antibacterial performance evaluation experiment, without external light source stimulation, CAP3 membrane can kill bacteria within 20 minutes (see Figure 6 CAP3 membrane can completely kill bacteria in just 90 seconds under simulated sunlight (see Figure 6 The test results of Figures C, D, G and H in the figure are shown in the figure); it meets the requirements of preparing multi-scenario protective materials with efficient antibacterial and real-time protective effects (regardless of the presence or absence of light source).
[0025] The prepared spinning membrane was used for mask protection, and the performance was compared with that of ordinary commercial masks. Staphylococcus aureus and Escherichia coli were selected as test objects. The results are shown in Figure 7 , where: Figure A is a digital image of Staphylococcus aureus cultured under lightless and lighted conditions on commercial masks and CAP3 masks, Figure B is a digital image of Escherichia coli cultured under lightless and lighted conditions on commercial masks and CAP3 masks, and Figure C is a digital image of PM2.5 on commercial masks and CAP3 masks. 2.5 and PM 10 The filtration effect diagram shows that the mask prepared by CAP3 membrane has excellent antibacterial properties (see Figure 7 A and B in Figure ), better particle filtering effect (see Figure 7 Figure C in the figure).
[0026] In order to consider the effect of practical application, we tested the photothermal heating effect of CAP3 film under natural sunlight and captured the image using an infrared camera. The results are shown in Figure 8 When exposed to sunlight, the temperature of the PAN film increased from the initial temperature of 11.1°C to 12.4°C after 3 hours, with a temperature change of 1.3°C. In contrast, the surface temperature of the CAP3 film increased slightly by 3.2°C. There was no obvious heat generation during the whole process, indicating that it would not cause thermal damage to the human body during normal outdoor use.
[0027] The antibacterial performance of CAP3 membrane was tested in cycles. The results are shown in Fig. 9 , where: Figure A is a digital image of Staphylococcus aureus and Escherichia coli cultured under lightless conditions, Figure B is a digital image of Staphylococcus aureus and Escherichia coli cultured under light-added conditions, Figure C is a graph of the antibacterial efficiency of Staphylococcus aureus and Escherichia coli cultured under lightless conditions, and Figure D is a graph of the antibacterial efficiency of Staphylococcus aureus and Escherichia coli cultured under light-added conditions. It was found that within 5 cycles, the antibacterial effect of the CAP3 membrane was almost unaffected under light and no light conditions, indicating that the CoO@Ag nanozyme would not easily leak from the fiber surface, further ensuring the safety of the wearer.
[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing CoO@Ag nanozyme, characterized in that: The following steps are involved: The cobalt salt and the stabilizer are dissolved in water to obtain a cobalt salt solution. A reducing agent is added to the cobalt salt solution and stirred for reaction. Then, a silver nitrate solution is added and stirred continuously. Finally, a quencher is added to quench the reaction. The obtained product is washed and dried and recorded as CoO@Ag nanozyme.
2. The method for preparing CoO@Ag nanozyme according to claim 1, characterized in that: The cobalt salt is cobalt nitrate, cobalt sulfate or cobalt chloride.
3. The method for preparing CoO@Ag nanozyme according to claim 1, characterized in that: The stabilizer is trisodium citrate.
4. The method for preparing CoO@Ag nanozyme according to claim 1, characterized in that: The reducing agent is sodium borohydride.
5. The method for preparing CoO@Ag nanozyme according to claim 1, characterized in that: The molar ratio of the cobalt salt to silver nitrate is (1-10):
1.
6. The method for preparing CoO@Ag nanozyme according to claim 1, characterized in that: The quenching agent is anhydrous ethanol.
7. A CoO@Ag nanozyme, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 6.
8. A method for preparing a functionalized fiber membrane, characterized in that: The following steps are involved: The polyacrylonitrile powder and the CoO@Ag nanozyme as described in claim 7 are dispersed in a solvent to obtain a mixed solution; after removing the bubbles in the mixed solution, a functionalized fiber membrane is prepared by using an electrospinning technology.
9. The functionalized fiber membrane prepared by the preparation method according to claim 8 is used as a sterilization and filtration intermediate layer in a mask.
Citation Information
Patent Citations
Nano-silver particle dispersed cobalt oxide optical film and preparation thereof
CN101376568A
Method for preparing nano-scale catalyst cobaltous oxide
CN105879873A
Preparation method of cobalt oxide modified Ag / TiO2 coaxial heterogeneous nanowire photocatalyst
CN106076363A
CoFe2O4-AgI Composite photocatalyst and preparation method thereof
CN107149936A
Nanometer Ag / CoO-N catalyst as well as preparation method and application thereof
CN107597167A